Intentionally self-injured patients have lower mortality when treated at trauma centers versus non-trauma centers in South Korea - Jin Woo; Han Zo Choi; Jongkyeong Kang (Trauma Surgery & Acute Care Open)
Objective This study investigated the characteristics and survival rates of patients with intentional severe trauma (self-harm or suicide) who were transported to either a regional trauma center (TC) or a non-TC facility.Methods This retrospective, national, population-based, observational, case-control study included patients who sustained intentional severe trauma and had an abnormal Revised Trauma Score at the injury site between January 2018 and December 2019. The data were a community-based severe trauma survey based on data collected from severe injury and multiple casualty patients transported by 119 emergency medical services (EMS), distributed by the Korea Disease Control and Prevention Agency. The treatment hospitals were divided into two types, TC and non-TCs, and several variables, including in-hospital mortality, were compared. Propensity score matching (PSM) was used to mitigate the influence of confounding variables on the survival outcomes.Results Among the 3864 patients, 872 and 2992 visited TC and non-TC facilities, respectively. The injury severity did not differ significantly between patients treated at TCs and non-TCs (TC, 9; non-TC, 9; p=0.104). However, compared with those treated at non-TCs, patients treated at TCs had a higher rate of surgery or transcatheter arterial embolization (14.2% vs 38.4%; p<0.001) and a higher admission rate to the emergency department (34.4% vs 60.6%; p<0.001). After PSM, 872 patients from both groups were analyzed. Patients treated at TCs exhibited a higher overall survival rate than those treated at non-TCs (76.1% vs 66.9%; p<0.001), and multiple variable logistic regression analysis demonstrated that the causes of injury and transport to the TC were significantly associated.Conclusion Using Korean EMS data, the results of this study revealed that initial transport to TCs was associated with reduced mortality rates. However, considering the limitations of using data from only 2 years and the retrospective design, further research is warranted.Study type Retrospective national, population-based observational case-control study.Level of evidence Level III